Association between Physical Activity and Cognitive Dysfunction in the Korean: A Cross-sectional Study - Sanghoon Jeong; Jae Yong Jang (Sapientia Publishing Group, 2017)
OBJECTIVES This study aimed to investigate the association of physical activity and cognitive function in the Korean population. METHODS This study included 9,177 adults aged 45 years and older who completed the baseline survey of the Korean Longitudinal Study of Ageing. Physical activity was assessed using a questionnaire. Cognitive function was assessed using the Mini Mental Status Evaluation. RESULTS The odds ratio for the cognitive dysfunction was significantly and linearly decreased according to the levels of physical activity independent of confounding factors. We also found consistent results when investigated these associations using stratified model by sex and age groups. CONCLUSIONS Our findings suggest that physical activity is associated with lower risk of cognitive dysfunction in the middle-aged and older Korean adults.